PENGARUH GREEN PRODUCT QUALITY DAN GREEN PERCEIVED RISK TERHADAP GREEN CUSTOMER SATISFACTION SERTA GREEN CUSTOMER LOYALTY PADA KONSUMEN PERTAMAX/ PERTAMAX PLUS DI KOTA MATARAM - Lalu Raditya P.R (Master of Management, Mataram University, 2015)
This research is entitled “The Effect of Green Product Quality and Green PerceivedRisk on Green Customer Satisfaction and Green Customer Loyalty in the Consumerof Pertamax/Pertamax Plus in Mataram”. The background of this research were thefindings of previous researches and some other theories sating that Green ProductQuality, Green Perceived Risk, Green Customer Satisfaction, and Green CustomerLoyalty are inter-related to one another. This research was aimed at determining theeffect of Green Product Quality and Green Perceived Risk on Green CustomerSatisfaction and Green Customer Loyalty in the consumer of Pertamax/PertamaxPlus in Mataram. This research is an associative research. The method of datacollection is survey sampling where the samples were selected through accidentalsampling with 120 respondents. The data were collected through observation,interview, and questionnaire. The method of data analysis is structural equationmodelling analysis with AMOS program. The research showed that all hypothesis inthis research are supported. Thus, it could be concluded that the variables of GreenProduct Quality and Green Perceived Risk affect the Green Customer Loyalty eitherdirectly or indirectly through Green Customer Satisfaction. It is suggested thatPertamina improve the quality of Pertamax as the Green Product, as well as reducethe risk that the consumers of Pertamax may perceive in the environment, withintense communication and socialization.Keywords: Green Product Quality, Green Perceived Risk, Green Customer Satisfaction, GreenCustomer Loyalty, Green Product